Effect of grilling and roasting on the fatty acids profile of chicken and mutton - Alina A.R.; Nurul Mawaddah A.H.; Siti Mashitoh A.; Shazamawati Z.H.; Nurulhuda M.S.; Ummi Syuhada H.S.; Imtinan A.K. (2024)
Indexed by SCOPUS